Spatial Weighted Mean Center for Infection, Recovered and Death Cases of COVID-19 in the Kingdom of Saudi Arabia - Alanazi, Humud Hadi; Qoradi, Mofareh (Journal of natural sciences, life and applied sciences, 2021)
The study aimed to determine the center of gravity of infection, recovered, and death of Covid-19 in KSA, and tracking the movement of the center of gravity. Also, we tried to reveal the factors that may affect the center of gravity and rout of the epidemic during the study period. The study used the quantitative approach and We applied the spatial analysis method. This method deals with the spatial phenomenon by studying and analyzing to get results that explain this phenomenon using the weighted mean center. It is one of the most important tools for measuring the spatial distribution of geographical phenomena. The study came out with several results. One of The most important results is determined the weighted mean center of infection cases. It is located to the east of the mean center of infection sites, while the weighted mean center of recovered cases located to the east of the mean center of recovery sites. On other hand, the weighted mean center for death cases is located west of the mean center of the death site. The number of deaths recorded in Makkah Al-Mukarramah, Jeddah, and Taif in the Makkah Region affects it.